Impact of substrate choice on human osteoclast differentiation and secretome: Implications for targeted therapeutic development - Fernanda D’Amélio; Hugo Vigerelli; Rodrigo Pinheiros Araldi; Adriana da Costa Neves; Álvaro Rossan de Brandão Prieto-da-Silva; Daniel Pimenta; Irina Kerkis (PLoS ONE, 2025)
Osteoclasts (OCs) exhibit substrate-specific molecular adaptations crucial for bone remodeling. We utilized mass spectrometry and functional enrichment analysis to delineate the proteomic profiles of mature polarized OCs cultured on mineralized versus plastic plates. Our findings reveal that mineralized surfaces promote the expression of proteins specialized for bone resorption and matrix interaction, such as lysosomal enzymes and ion transporters. This environment induces a mature and resorptive phenotype in OCs, enriched in pathways like VEGF/VEGFR signaling and various cytokine pathways. Conversely, OCs on plastic plates display a more diverse proteomic profile, highlighting adaptations in adhesion, proliferation, and stress response pathways, suggesting a focus on cellular maintenance rather than active resorption. Key therapeutic targets for osteoclastogenesis include components of the Hedgehog (Hh) pathway—SHH, DHH, and IHH—with Smoothened (SMO) integral to Hh signaling in OC differentiation. Additionally, Guanine Nucleotide Exchange Factors (GEFs), significantly enriched on plastic plates, are crucial for adapting to non-mineralized environments. Other notable targets include molecular regulators such as NCOR2, which modulates gene expression; NOS1, involved in nitric oxide production and OC function; and XIAP, which influences cell survival. Chromatin remodeling proteins like TACC2 and signaling pathways involving IRS1, MSX1, and AKT are also highlighted. The targets identified in this study are specific to polarized OCs and may not apply to non-polarized OCs or other cell types. These findings underscore the complexity of OC differentiation and function, enhancing our understanding of substrate-specific adaptations and suggesting new strategies for modulating bone metabolism and addressing bone-related disorders.